Organic Product Awareness and Healthy Life Preferences of Iğdır University Students: Investigation with Machine Learning and AHP Analysis - SAHIN DEMIREL, Ayca Nur; TURK , Sema (ISPEC Tarım Bilimleri Dergisi, 2024)
The aim of this study is to analyze the demographic structure, knowledge level about organic products and healthy lifestyle preferences of students of Iğdır University. In the study, a face-to-face survey was conducted on 300 students. RStudio program was used to analyze the data and machine learning method with XGBoost algorithm was preferred. The participants of the survey were 53.7% male and 46.3% female. Most of the participants are in the age group of 21-22 years (32.7%) and are students in formal education (85.3%). It was observed that the higher the number of siblings, the lower the level of education. There is a positive correlation between family income and educational level. The factors that most influence the knowledge of organic products are the number of siblings, fast food diet and family income. As family income increases, so does awareness of organic products. The majority of participants correctly define organic products. AHP analysis revealed that being physically healthy in the future is more important than being physically healthy now. The relationship between organic products and physical health stands out as an important result. The Friedman test confirms that the AHP analysis has produced a successful result with a high degree of accuracy.